Hedging price risks of farmers by commodity boards : A simulation applied to the Indian Natural rubber market - Zant Wouter (World Development, 2001)
This paper investigates a hypothetical hedging scheme in a domestic commodity market under which a commodity board offers a forward contract to domestic producers and local traders and covers its commitments on an international futures exchange. It is aimed to quantify welfare gains to agents in the market and costs and benefits of the board empirically. The empirical work is based on the Indian natural rubber market and the Tokyo Commodity Exchange (TOCOM) for the period 1990-95. The hedging scheme is shown to increase welfare substantially, particularly welfare of growers. The costs of such a facility for the commodity board (basis risk) are negligible. If the forward price offered on the domestic market is a small fraction below the international futures price, the board can prevent losses at only slightly lower welfare gains.
Keywords: Asia; Commodities; India; Risk; Rubber market